Factors affecting tertiary English learners' persistence in the self-directed language learning journey. (August 2018) - Cheng, Adrienne; Lee, Cynthia
Abstract: The aim of the study is to identify the factors that influence tertiary students' continuation and completion of a self-directed English learning scheme at a university in Hong Kong. The study collected and analyzed both quantitative and qualitative data based on 76 students' attendance records provided by language advisors, 27 completed online questionnaires, and seven interviews with purposively selected students. The findings revealed some factors that influenced students' engagement in independent language learning. They indicated that despite students' increasing wish to become proficient in English, their efforts to engage in language learning decreased over the course of the semester. Students' busy study schedules and the tough requirements of the scheme were identified as the major causes of demotivation among the participants. In contrast, continuous advisor and peer support and evidence of progress contributed to student persistence in the learning process. Another factor that distinguished motivated learners from less motivated learners was their level of autonomous behavior. Some recommendations are made to support teaching and learning in similar language support schemes in higher education to help sustain and promote students' interest in self-directed language learning.